Turismo ecológico y su impacto en los habitantes de la Isla Sani, Provincia de Sucumbíos año 2022 - Ruperty Tumbaco, Romina Rebecca (2022)
The purpose of this project is to present ecological tourism and its impact on the inhabitants of Sani Island, province of Sucumbíos, which has a wide variety of natural attractions, and to identify the current state of ecological tourism, which allows the community to organize itself and seek a better quality of life through activities such as the development of ecotourism. The study of the impact of ecotourism on the inhabitants of Sani Island is fundamental before making decisions that may be irreversible, since it is about knowing the positive and negative aspects that a decision related to an investment for development may have on the natural and social environment in order to take the necessary precautions. With the support of the inhabitants of Sani Island, in the province of Sucumbíos, it will be possible to provide quality services and this will influence the ecotourism, economic and social development of the community since, with its environmentally friendly infrastructure, many tourists will choose this site as a vacation option and they will also learn more about ecotourism, as well as provide excellent service to people so they can feel satisfied and decide to return to the place. The main objective of this work is to propose some methodological guidelines to incorporate ecotourism in the decisions that affect the investment process in rural tourist areas, taking as a reference the impact of the inhabitants of Sani Island.